Sustainable soil treatment: Investigating the efficacy of carrageenan biopolymer on the geotechnical properties of soil - Fatehi, Hadi; Ong, Dominic E.L.; Yu, Jimmy; Chang, Ilhan (Construction and Building Materials, 2024)
The employment of novel biopolymers offers geotechnical engineers a diverse range of materials to choose from, depending on the specific requirements of different projects. Regarding the promotion of environmentally friendly materials in the construction industry, this study introduces carrageenan as a novel biopolymer for soil improvement. The research also includes a comparative study of carrageenan's performance with xanthan which is the most commonly used biopolymer in geotechnical engineering. Unconfined compressive tests (UCS) were conducted to evaluate the performance of biopolymer-treated soil samples over a variety of effective parameters including biopolymer content, moisture content, curing time, soil particle size, and durability under wet-dry cycles. In order to explore the soil size effect, kaolinite silt and sand were combined in various proportions and treated with different biopolymer ratios to enhance strength development. The optimal mix of each biopolymer-treated soil was then exposed to five cycles of wetting and drying. Carrageenan improved the compressive strength of untreated soils in all cases, for example 3.4 times for 0.5% (wb/ws) of biopolymer. In higher proportions of kaolinite, carrageenan performed considerably better than xanthan gum in terms of compressive and shear strength. In addition, with an emphasis on confining pressures, static triaxial experiments were conducted to examine the effectiveness of carrageenan, by which it was shown that carrageenan outperforms xanthan in terms of shear strength especially in the fine-grained soil. The mechanism and chemical interaction behind the significant performance of carrageenan in binding soil grains, increasing mechanical strength and improving durability of the soil was also studied through FTIR analysis and scanning electron microscopy (SEM) images. It can be concluded that carrageenan can be considered as a sustainable alternative to conventional materials such as cement and lime.
Keywords: Biopolymer treated soil; Carrageenans; FTIR; Geotechnical properties; Performance; Shears strength; Soil treatments; Static triaxial test; Treated soils; Unconfined compressive strength; Biopolymer treated soil; Carrageenan; FTIR; SEM; Static triaxial test; Unconfined compressive strength